PENGARUH KEPEMIMPINAN DAN KOMPETENSI KARYAWAN TERHADAP KINERJA KARYAWAN CV. INDONESIA LIVE GARMENT BIDANG PRODUKSI BAGIAN SEWING, KABUPATEN SRAGEN - Permatasari, Lily Desianti; DS, Agus Hermani (Jurnal Ilmu Administrasi Bisnis, 2020)
CV. Indonesia Live Garment is a garment company that working on clothing and pants orders from domestic and foreign brands. However, there are still employees who have low performance such as employees unable to achieve targets, the products produced are not in accordance with quality, and can not complete their work on time. This is allegedly because leadership has not been implemented properly and employee competencies are still low. This study aims to determine the effect of leadership and employee competence on the performance of sewing employees in the CV. Indonesia Live Garment. The type of research used is explanatory research. The sample used as many as 50 respondents in the sewing department employees CV. Indonesia Live Garment. Data collection using a questionnaire with a likert measurement scale. The results showed that the leadership and employee competency variables partially influenced employee performance positively and significantly with the regression coefficient values on the leadership variable (0.355) and employee competence (0.415) and the t-value of the leadership variable (2,593) and employee competency (3,085) ) affect employee performance positively and significantly with the multiple regression coefficient values of leadership variables (0.320) and employee competencies (0.385) with F-count (8.433).